'You say you are a TB doctor, but actually, you do not have any power': health worker (de)motivation in the context of integrated, hospital-based tuberculosis care in eastern China - Guanyang Zou; Barbara McPake; Karina Kielmann (BMC, 2022)
Abstract Background In China, tuberculosis (TB) care, traditionally provided through the Centre for Disease Control (CDC), has been integrated into 'designated' public hospitals at County level, with hospital staff taking on delivery of TB services supported by CDC staff. Little is known about the impact of this initiative on the hospital-based health workers who were delegated to manage TB. Drawing on a case study of two TB 'designated' hospitals in Zhejiang province, we explored factors influencing hospital-based health workers' motivation in the context of integrated TB service delivery. Methods We conducted 47 in-depth interviews with health officials, TB/hospital managers, clinicians, radiologists, laboratory staff and nurses involved in the integrated model of hospital-based TB care. Thematic analysis was used to develop and refine themes, code the data and assist in interpretation. Results Health workers tasked with TB care in 'designated' hospitals perceived their professional status to be low, related to their assessment of TB treatment as lacking need for professional skills, their limited opportunities for professional development, and the social stigma surrounding TB. In both sites, the integrated TB clinics were under-staffed: health workers providing TB care reported heavy workloads, and expressed dissatisfaction with a perceived gap in their salaries compared with other clinical staff. In both sites, health workers were concerned about poor infection control and weak risk management assessment systems. Conclusions Inadequate attention to workforce issues for TB control in China, specifically the professional status, welfare, and development as well as incentivization of infectious disease control workers has contributed to dissatisfaction and consequently poor motivation to serve TB patients within the integrated model of TB care. It is important to address the failure to motivate health workers and maximize public good-oriented TB service provision through improved government funding and attention to the professional welfare of health workers providing TB care in hospitals.